A cluster randomised trial of educational messages to improve the primary care of diabetes - Foy, Robbie; Eccles, Martin P; Hrisos, Susan; Hawthorne, Gillian; Steen, Nick; Gibb, Ian; Croal, Bernard; Grimshaw, Jeremy (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background Regular laboratory test monitoring of patient parameters offers a route for improving the quality of chronic disease care. We evaluated the effects of brief educational messages attached to laboratory test reports on diabetes care. Methods A programme of cluster randomised controlled trials was set in primary care practices in one primary care trust in England. Participants were the primary care practices' constituent healthcare professionals and patients with diabetes. Interventions comprised brief educational messages added to paper and electronic primary care practice laboratory test reports and introduced over two phases. Phase one messages, attached to Haemoglobin A1c (HbA1c) reports, targeted glycaemic and cholesterol control. Phase two messages, attached to albumin:creatinine ratio (ACR) reports, targeted blood pressure (BP) control, and foot inspection. Main outcome measures comprised practice mean HbA1c and cholesterol levels, diastolic and systolic BP, and proportions of patients having undergone foot inspections. Results Initially, 35 out of 37 eligible practices participated. Outcome data were available for a total of 8,690 patients with diabetes from 32 practices. The BP message produced a statistically significant reduction in diastolic BP (-0.62 mmHg; 95% confidence interval -0.82 to -0.42 mmHg) but not systolic BP (-0.06 mmHg, -0.42 to 0.30 mmHg) and increased the odds of achieving target BP control (odds ratio 1.05; 1.00, 1.10). The foot inspection message increased the likelihood of a recorded foot inspection (incidence rate ratio 1.26; 1.18 to 1.36). The glycaemic control message had no effect on mean HbA1c (increase 0.01%; -0.03 to 0.04) despite increasing the odds of a change in likelihood of HbA1c tests being ordered (OR 1.06; 1.01, 1.11). The cholesterol message had no effect (decrease 0.01 mmol/l, -0.04 to 0.05). Conclusions Three out of four interventions improved intermediate outcomes or process of diabetes care. The diastolic BP reduction approximates to relative reductions in mortality of 3% to 5% in stroke and 3% to 4% in ischaemic heart disease over 10 years. The lack of effect for other outcomes may, in part, be explained by difficulties in bringing about further improvements beyond certain thresholds of clinical performance. Trial Registration Current Controlled Trials, ISRCTN2186314.